Contribution to the tribe Pentoffiini (Cicadellidae: Evacanthinae) with descriptions of two new species and the male of Evanirvana aurea Hill, 1973 - Gonçalves, Clayton C.; Dietrich, Christopher H.; Takiya, Daniela M. (Zootaxa, 2019)
Pentoffiini is a small tribe of Neotropical leafhoppers that includes two genera: Evanirvana Hill, 1973 with only one species, E. aurea, previously known only from females and Pentoffia Kramer, 1964 with seven species. Here, we describe the male of E. aurea, a new species of Evanirvana, E. tambopata sp. nov., from Peru, and a new species of Pentoffia, P. santosi sp. nov., from Peru. A revised diagnosis for Evanirvana and key to all known species of Pentoffiini are provided.